Analytical View on the Financial and Social Stability within the Euro Area: Empirical Evidence from Slovakia - Kiselakova, Dana; Sofrankova, Beata; Soltes, Miroslava (International Journal of Economics and Financial Issues, 2016)
This paper analyses global risks with focus on factors affecting macroeconomic development in regard to financial and social stability in empirical models from aspect of bank’s credibility, in the economy of Slovakia within the euro area. The relationships between the dependence of the financial stability, risk factors and macroeconomic development have been surveyed spanning a period of fourteen years (2001-2014) through the methodology of construction of multiple linear regression models. Established factors of credibility in empirical models - the model of net profit as a model of bank’s credibility and the model of capital adequacy as a model of the financial soundness - show common features for other economies. The important risk factor is the growth in the share of non-performing loans of customers and increasing unemployment rate in the economy, as one of the biggest problems in the EU. Empirical models can be applied in other countries and present implications for economic decision-making with focus on decreasing unemployment rate. Keywords: Financial and social stability, Risks and factors of bank’s credibility, Regression models JEL Classifications: C23, G30, G32